Molecular and Functional Diversity of GABA-A Receptors in the Enteric Nervous System of the Mouse Colon - Seifi, Mohsen (Society for Neuroscience, 2014)
The enteric nervous system (ENS) provides the intrinsic neural control of the gastrointestinal tract (GIT) and regulates virtually all GI functions. Altered neuronal activity within the ENS underlies various GI disorders with stress being a key contributing factor. Thus, elucidating the expression and function of the neurotransmitter systems, which determine neuronal excitability within the ENS, such as the GABA-GABA(A) receptor (GABA(A)R) system, could reveal novel therapeutic targets for such GI disorders. Molecular and functionally diverse GABA(A)Rs modulate rapid GABAergic-mediated regulation of neuronal excitability throughout the nervous system. However, the cellular and subcellular GABA(A)R subunit expression patterns within neurochemically defined cellular circuits of the mouse ENS, together with the functional contribution of GABA(A)R subtypes to GI contractility remains to be determined. Immunohistochemical analyses revealed that immunoreactivity for the GABA(A)R gamma (γ) 2 and alphas (α) 1, 2, 3 subunits was located on somatodendritic surfaces of neurochemically distinct myenteric plexus neurons, while being on axonal compartments of submucosal plexus neurons. In contrast, immunoreactivity for the α4–5 subunits was only detected in myenteric plexus neurons. Furthermore, α-γ2 subunit immunoreactivity was located on non-neuronal interstitial cells of Cajal. In organ bath studies, GABA(A)R subtype-specific ligands had contrasting effects on the force and frequency of spontaneous colonic longitudinal smooth muscle contractions. Finally, enhancement of γ2-GABA(A)R function with alprazolam reversed the stress-induced increase in the force of spontaneous colonic contractions. The study demonstrates the molecular and functional diversity of the GABA(A)R system within the mouse colon providing a framework for developing GABA(A)R-based therapeutics in GI disorders.